2013
DOI: 10.1016/j.carbpol.2013.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Multiple complexation of cyclodextrin with soy isoflavones present in an enriched fraction

Abstract: In the present study we evaluated the complexation of daidzein/genistein/glycitein, present in an isoflavone enriched fraction (IEF), with β-cyclodextrin and 2-hydroxypropyl-β-cyclodextrin (HPβCD). Based on the increased solubility and higher complexation efficiency, IEF and HPβCD solid complexes were prepared by kneading, freeze-drying, co-evaporation, spray-drying and microwave. The solid complexes were characterized using Fourier transformed-infrared spectroscopy, differential scanning calorimetry, X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In general, CD derivatives such as HPβCD were more efficient as complexation agents compared to parent βCD and, in many cases, an increased antioxidant capacity of CD encapsulated polyphenols was observed [16,17]. Taking all of this into account, it seems that the use of CD aqueous solutions as an extraction medium could be a valid approach to efficiently extract bioactive compounds from the plant material, especially taking into account the results of Yatsu et al [18], who demonstrated the possibility of the simultaneous complexation of daidzein, genistein, and glycitein from an enriched soy fraction with the HPβCD. An additional benefit of the CD-based extraction could be in their ability to chemically stabilize sensitive molecules by inclusion complex formation, considering that ultrasound may trigger or accelerate some chemical reaction in the sample, such as degradation of phenolic acids as well as degradation and oxidation of flavonoids [19].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In general, CD derivatives such as HPβCD were more efficient as complexation agents compared to parent βCD and, in many cases, an increased antioxidant capacity of CD encapsulated polyphenols was observed [16,17]. Taking all of this into account, it seems that the use of CD aqueous solutions as an extraction medium could be a valid approach to efficiently extract bioactive compounds from the plant material, especially taking into account the results of Yatsu et al [18], who demonstrated the possibility of the simultaneous complexation of daidzein, genistein, and glycitein from an enriched soy fraction with the HPβCD. An additional benefit of the CD-based extraction could be in their ability to chemically stabilize sensitive molecules by inclusion complex formation, considering that ultrasound may trigger or accelerate some chemical reaction in the sample, such as degradation of phenolic acids as well as degradation and oxidation of flavonoids [19].…”
mentioning
confidence: 89%
“…The dissolved molecules would be able to interact with HPβCD present in the extraction medium according to their corresponding affinity. The simultaneous CD complexation of several different molecules was already demonstrated for isoflavones present in an enriched soy fraction [18] as well as in the case of ferulic and galic acid coencapsulation in HPβCD [30]. After equilibration of the system, the components that form the most stabile complexes with HPβCD would remain in the solution, thus being more efficiently extracted.…”
mentioning
confidence: 95%
“…Genistein ability to cross biological membranes was also improved by the encapsulation with the CDs [59]. β-CD and HP-β-CD IC formation was investigated with a mixture of daidzein, genistein and glycitein [60]. All the isoflavones showed the highest affinity with HP-β-CD and the interaction between the CD and the bioactive molecules occur by insertion of the B-ring into the CD cavity [60].…”
Section: Cyclodextrins Inclusion Complexesmentioning
confidence: 99%
“…One of the major limitations of using natural products is a reduced water solubility and bioavailability of the molecules of interest. An innovative strategy to overcome such challenges is their complexation with cyclodextrins; in other words, the formation of inclusion complexes to increase the water solubility of the plant compound [23]. This molecular property has enabled the use of cyclodextrins in different applications in science and technology, mainly in the pharmaceutical industry, by virtue of obtaining new drugs with different physical and chemical properties with the same active compounds [24].…”
Section: Introductionmentioning
confidence: 99%